Growth Optimization and Device Integration of Narrow‐Bandgap Graphene Nanoribbons (Small 31/2022). Issue 31 (4th August 2022) - Borin Barin, Gabriela; Sun, Qiang; Di Giovannantonio, Marco; Du, Cheng‐Zhuo; Wang, Xiao‐Ye; Llinas, Juan Pablo; Mutlu, Zafer; Lin, Yuxuan; Wilhelm, Jan; Overbeck, Jan; Daniels, Colin; Lamparski, Michael; et al.
Abstract : Graphene Nanoribbons This work studies the growth, characterization, and device integration of 5‐armchair graphene nanoribbons (GNRs). 5‐AGNRs are synthesized under ultrahigh vacuum conditions from Br‐ and I‐substituted precursors. In article number 2202301, Gabriela Borin Barin, Pascal Ruffieux, and co‐workers show that I‐substituted precursors and optimized initial precursor coverage quintuple the average 5‐AGNR length. This significant length increase allows the authors to integrate 5‐AGNRs into field‐effect transistors, showing switching behavior at room temperature.